PwC Involved in Evergrande Financial Scandal: An Ethical Crisis for the Auditing Profession? - Insirat, Mutahira Nur; Masnia, Masnia; Amiruddin, Amiruddin; Syamsuddin, Syamsuddin (Program Studi Akuntansi FPEB UPI, 2024)
This article discusses PricewaterhouseCoopers' (PwC) involvement in the Evergrande financial scandal and its implications for the audit profession. The scandal exposed PwC's failure to detect and report significant financial discrepancies that led to the collapse of Evergrande, one of China's largest property developers with more than 300 billion in debt. The findings highlight weaknesses in the audit process as well as a lack of effective regulatory oversight. PwC, as one of the Big Four accounting firms, faced severe sanctions in the form of a 62 million fine and a six-month ban on operating in China. The article also explores how the scandal exacerbated the loss of public trust in the auditing profession, which is perceived as failing to maintain the integrity of financial reporting. This analysis offers important lessons about the need to strengthen ethical rules, auditor independence, and accountability in the audit process. In addition, the research recommends reforms in oversight and corporate governance to prevent similar crises in the future. This article is expected to contribute to efforts to improve audit quality and restore public confidence in the global financial system.